Distinct Predatory Behaviors in Scimitar- and Dirk-Toothed Sabertooth Cats. - Figueirido-Castillo, Francisco Borja; Lautenschlager, Stephan; Pérez-Ramos, Alejandro; Van Valkenburgh, Blaire (Cell Press, 2018)
Over the Cenozoic, large cat-like forms have convergently evolved into specialized killers of “megaherbivores” that relied on their large, and laterally compressed (saber-like) canines to rapidly subdue their prey. Scimitar- and dirk-toothed sabertooths are distinct ecomorphs that differ in canine tooth length, degree of serration, and postcranial features indicative of dissimilar predatory behavior. Despite these differences, it is assumed that they used a similar “canine-shear” bite to kill their prey. We investigated the killing behavior of the scimitar-toothed Homotherium serum and the dirk-toothed Smilodon fatalis using a comparative sample of living carnivores and a new quantitative approach to the analysis of skull function. For the first time, we quantified differences in the relative amount and distribution of cortical and trabecular bone in coronal sections of skulls to assess relative skull stiffness and flexibility. We also use finite element analysis to simulate various killing scenarios that load skulls in ways that likely favor distinct proportions of cortical versus trabecular bone across the skull. Our data reveal that S. fatalis had an extremely thick skull and relatively little trabecular bone, consistent with a large investment in cranial strength for a stabbing canine-shear bite. However, H. serum had more trabecular bone and most likely deployed an unusual predatory behavior more similar to the clamp-and-hold technique of the lion than S. fatalis. These data broaden the killing repertoire of sabertooths and highlight the degree of ecological specialization among members of the large carnivore guild during the Late Pleistocene of North America.
Keywords: Método de los elementos finitos; Paleobiología; Dientes fósiles; Félidos fósiles; Cranial biomechanics; Cortical bone; Trabecular bone; Finite element analysis; Paleobiology; Killing bite; Dirk-tooths; Scimitar-tooths